The Woman Question in Islamic Studies By Kecia Ali - Flodin-Ali, Yasmine (Journal of the American Academy of Religion, 2025)
In Kecia Ali’s book The Woman Question in Islamic Studies, the woman question is twofold: 1) are women fairly represented in Islamic Studies as subject mat